Ipsilesional Motor Cortex Activation with High-force Unimanual Handgrip Contractions of the Less-affected Limb in Participants with Stroke. (10th February 2022) - Andrushko, Justin W.; Gould, Layla; Renshaw, Doug W.; Forrester, Shannon; Kelly, Michael E.; Linassi, Gary; Mickleborough, Marla; Oates, Alison; Hunter, Gary; Borowsky, Ron; Farthing, Jonathan P.
Highlights: Non-paretic high-force contractions promote ipsilesional motor cortex activation. Brain activation was similar between healthy controls and participants with stroke. Non-paretic high-force contractions may provide a boost for ipsilesional plasticity. Abstract: Stroke is a leading cause of severe disability that often presents with unilateral motor impairment. Conventional rehabilitation approaches focus on motor practice of the affected limb and aim to suppress brain activity in the contralesional hemisphere. Conversely, exercise of the less-affected limb promotes contralesional brain activity which is typically viewed as contraindicated in stroke recovery due to the interhemispheric inhibitory influence onto the ipsilesional hemisphere. Yet, high-force unimanual handgrip contractions are known to increase ipsilateral brain activation in control participants, and it remains to be determined if high-force contractions with the less-affected limb would promote ipsilateral brain activation in participants with stroke (i.e., the ipsilesional hemisphere). Therefore, this study aimed to determine how parametric increases in handgrip force during repeated contractions with the less-affected limb impacts brain activity bilaterally in participants with stroke and in a cohort of neurologically intact controls. Participants performed repeated submaximal contractions at 25%, 50%, and 75% of their maximum voluntary contraction during separate functional magnetic resonance imaging brain scans. Brain activation during the tasks was quantified as the percent change from resting levels. In this study, higher force contractions were found to increase brain activation in the ipsilesional (stroke)/ipsilateral (controls) hemisphere in both groups ( p  = .002), but no between group differences were observed. These data suggest that high-force exercise with the less-affected limb may promote ipsilesional cortical plasticity to promote motor recovery of the affected-limb in participants with stroke.